The bishop of Winchester, the abbey of Titchfield and the ‘Pretended Chapel’ of Hook, 1375–1405 - Given-Wilson, Chris (People, Power and Identity in the Late Middle Ages: Essays in Memory of W. Mark Ormrod, 2021)
The first known reference to it is dated 15 March 1364, when Pope Urban V ordered Bishop Edington of Winchester to inquire into a petition from the inhabitants of Hook proposing the foundation of a chapel there. The problem was that neither Bishop Wykeham nor the abbot of Titchfield to whom the parish church had been appropriated since the abbey's foundation in 1232 supported the construction of a chapel at Hook; and therein lay the origins of the dispute. The contention of the abbot of Titchfield, John de Thorney, supported by Wykeham, was that the chapel at Hook prejudiced the rights of both the abbey and the parish church. At some point during the later fifteenth century, the chapel for which William Maple, John Michol and the villagers had fought so doggedly seems simply to have become surplus to requirements, and by the time Titchfield Abbey was suppressed in 1537 it was barely even a memory.
Num Pages: 20
Keywords: titchfield

The Last Days of the Abbeys of Durford and Titchfield and a Case of Mistaken Identity - Stevenson, Janet H. (Proceedings of the Hampshire Field Club and Archaeological Society, 2016)
Keywords: durford; titchfield

Two dated monastic buildings at Titchfield - Roberts, Edward (Hampshire studies, 2000)
Keywords: titchfield